Étude des propriétés électriques et optoélectroniques de diodes à puits quantiques AlxGa1-xAs/GaAs. - Richard, Paul G. (University of Ottawa (Canada), 1989)
Double barrier heterostructures of Al$\sb{\rm x}$Ga$\sb{\rm 1-x}$As/GaAs are studied. The presence of a quantized level in the well is confirmed by the observation of a region of negative differential resistance (NDR) in the current-voltage (I-V) characteristics of the heterostructures. A spectrum analyser and a network analyser are thus used to measure the oscillator properties of the samples and to investigate the effects of the external circuit on these properties and on the I-V characteristics. For the sample with AlAs barriers, electron oscillations, of frequency greater than 1 GHz, are measured at room temperature; the observation of these frequencies depends on the matching of the impedances of the external circuit to the device under test. Photoconductivity spectra and photocurrent-voltage (PC-V) characteristics at fixed wavelengths are measured in order to study the effects of light incident on the sample. I-V measurements are carried out in a quantizing magnetic field parallel to the tunneling current. With increasing magnetic field, the voltage periodic structures are shifted to higher bias positions at a similar rate of change. (Abstract shortened by UMI.)
Keywords: Physics, Condensed Matter.